Does the Brain Care Which Direction We Read? A Cross‐Cultural tDCS Study on Functional Lateralization of Number Processing - Narjes Bahreini; Christina Artemenko; Christian Plewnia; Reza Rostami; Hans‐Christoph Nuerk (Brain and Behavior)
ABSTRACT Purpose The potential influence of culture on functional lateralization was rarely investigated, yet it may be an important factor in our understanding of the human brain. In numerical processing, evidence was found for differential directional preferences of space–number associations in cultures with opposite reading direction systems. This may affect finger‐counting preferences like the starting hand, which in turn have previously been associated with differing lateralization. Such studies raise the question of whether number culture may also play a distinct role in the lateralization of the intraparietal sulcus (IPS), the hallmark region of numerical magnitude processing. Method In our preregistered cross‐cultural study, we applied anodal transcranial direct current stimulation (tDCS) over the left versus right IPS to investigate the effect of stimulation as compared to sham in Iranians (with right‐to‐left reading system) and Germans (with left‐to‐right reading system). Finding Results indicated no overall effect of stimulation; however, exploratory analyses revealed that tDCS over the left and right IPS facilitated number processing in Iranians compared to Germans after controlling for training effects. Finger‐counting direction was not found to be decisive for this effect. Conclusion At the end, number processing might be bilaterally represented in the IPS; however, our exploratory analyses emphasize the need for further investigation on the potential role of culture in the representations of numbers.